The Effect of Work Motivation on Employee Performance at Bukit Raya Sekawan Mining Company - Pratama, Yudhistira Anugerah; Yuliaty, Farida; Kosasih, Kosasih; Kadarisman, Sumeidi; Paramarta, Vip (Adpebi International Journal of Multidisciplinary Sciences, 2025)
The aim of this study is to examine the relationship between job motivation and employee performance at Bukit Raya Sekawan Mining Company. A quantitative associative technique was used in this study. This study's population consists of all 45 employees of Bukit Raya Sekawan Mining Company. Then, as tools and procedures for collecting data, observation, interviews, literature reviews, documentation studies, observation guidelines, and questionnaires are used. The results demonstrated that job motivation has a favorable and significant influence on staff performance at Bukit Raya Sekawan Mining Company. Therefore, Bukit Raya Sekawan Mining Company has to monitor and evaluate staff performance in order to ensure that corporate goals are met to the fullest and employee welfare is ensured. To guarantee a fair allocation of jobs, encourage collaboration among staff members, and provide opportunities for professional growth, Bukit Raya Sekawan Mining Company needs to collect accurate data. This is how it is expected that in the future, Bukit Raya Sekawan Mining Company and its employees would collaborate to fulfill their rights, obligations, and aspirations as one single unit.